Real Time Vehicle Tracking System for Smart Cities - Rudramurthy, M.S.; Hegde, Nitin; Tanmay, K; M, Santosh; Jawaid, Md. Sufian; A, Sushma S; G, Keerthan Kumar T (2023 International Conference on Data Science and Network Security (ICDSNS), 2023)
A vehicle tracking system is used to track the movement of a vehicle from anywhere at any time. The proposed system uses popular technologies integrating a smartphone system with a small controller. The automotive device is operated using the Global Positioning System (GPS) and the mobile communications system. The Google Maps API displays a vehicle on a map in a smartphone app. Thus, users can continuously monitor the moving vehicle utilizing the smartphone system and determine the minimum distance and time to reach a specific destination. Once the vehicle reaches a geofenced area, the users who have installed the application will receive a notification. When the GPS-enabled driver's smartphone enters the geofenced area, the user gets a notification, and when user leaves it, user receives another message indicating that user has finished his work. The user will be able to follow the smart city car's location, and if user taps on it, the user will be shown the precise distance between the vehicle and its present location. Users of this program can also browse the news, change their profiles, and record grievances.